TEACHERS' AND STUDENTS' PERSPECTIVES ON THE IMPLEMENTATION OF LESSON STUDY :A CASE STUDY RESEARCH AT ONE OF TEACHER CLUSTERS IN KABUPATEN BANDUNG BARAT - Anna Halillah, - (2011)
This study is a case study which investigates teachers' and students' perspectives on the implementation of lesson study. This study also explores teachers' difficulties in implementing lesson study. The study was conducted at one of teachers cluster in Kabupaten Bandung Barat and participated by ten English teachers and 37 junior high school students. For its framework for analysis, this study employs both qualitative and quantitative approaches to answer the research questions. To obtain the data, interview and questionnaire were used. Then the data were analyzed by comparing them with the related theories, including the definition of lesson study, the characteristics and strength of lesson study, the steps of lesson study and the benefits of lesson study and the difficulties faced by the teachers during the implementation of lesson study. Moreover, the data from questionnaire were analyzed by using Microsoft Excel to calculate the frequency and percentage of the data. The data from interview and questionnaire show that teachers still lacked understanding of lesson study. They could not explain comprehensively about lesson study. However, the teachers felt the benefits of lesson study, in terms of improving their teaching and sharing knowledge with other teachers. Moreover, regarding difficulties in implementing lesson study, data indicate that teachers faced limitation in scheduling and reflecting the result of the observation. As to students' perspectives on lesson study, this study finds out that students were conscious of the benefits of lesson study. Lesson study has helped their teacher to develop a more interesting learning activity by using the media and group work in the classroom. It is recommended that the teachers involve in the training of lesson study regularly to make lesson study activity better in the future.